Attitude and performance in English" a case for S.M.K Muara Tuang - Tee, Beng Chen (Universiti Malaysia Sarawak, (UNIMAS), 1997)
The objective of this research was to find out the relationship between attitude and performance in English. 100 students from a school in Kota Samarahan, Sarawak had participated in this research. The researcher administered a set of attitude test to elicit data. The students' PMR English results were used as the indicator of their performance in the language. An analysis was done by employing the Pearson Correlation Coefficients test. The findings of this research shows a moderate to favourable attitude towards English, but no correlation seems to exist as indicated by students' poor performance in the PMR English examination. Thus, it is proven that students' attitude and all other affecting variables can go either way in determining students' performance in second language learning. Some suggestions were recommended for researchers to conduct future researches in a more widespread and effective ways.